2010
DOI: 10.1007/s00284-010-9642-1
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Bacteria Improve Seedling Growth of Sunflower Under Water Stress, Produce Salicylic Acid, and Inhibit Growth of Pathogenic Fungi

Abstract: Endophytic bacterial strains SF2 (99.9% homology with Achromobacter xylosoxidans), and SF3 and SF4 (99.9% homology with Bacillus pumilus) isolated from sunflower grown under irrigation or drought were selected on the basis of plant growth-promoting bacteria (PGPB) characteristics. Aims of the study were to examine effects of inoculation with SF2, SF3, and SF4 on sunflower cultivated under water stress, to evaluate salicylic acid (SA) production by these strains in control medium or at Ψa = -2.03 MPa, and to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(38 citation statements)
references
References 31 publications
1
32
0
2
Order By: Relevance
“…The use of antagonist rhizobacteria belonging to Bacillus genus showed to stimulate plant growth and to increase crop yield of tomato (Hernandez-Suarez et al, 2011). Endophytic Science Publications AJABS bacterial strains SF2 (99.9% homology with Achromobacter xylosoxidans) and SF3 and SF4 (99.9% homology with B. pumilus) enhanced growth of sunflower seedlings under water stress and inhibited growth of pathogenic fungi (Forchetti et al, 2010). Tariq et al (2009) reported the dual role of Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of antagonist rhizobacteria belonging to Bacillus genus showed to stimulate plant growth and to increase crop yield of tomato (Hernandez-Suarez et al, 2011). Endophytic Science Publications AJABS bacterial strains SF2 (99.9% homology with Achromobacter xylosoxidans) and SF3 and SF4 (99.9% homology with B. pumilus) enhanced growth of sunflower seedlings under water stress and inhibited growth of pathogenic fungi (Forchetti et al, 2010). Tariq et al (2009) reported the dual role of Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, direct observation of the seedling showed that the seedling was more stout and fresh. Some bacterial control agent produce plant growth regulator to increase plant performance (Forchetti et al, 2010;Hernandez-Suarez et al, 2011). Fusarium wilt caused unhealthy seedlings by reducing seedling height to 6.08 cm and dry-weight to 2.42 g.…”
Section: Chili Damping Off Suppressionmentioning
confidence: 99%
“…Currently, endophytic bacteria are attracting increasing attention not only for their promotion of plant growth and control of plant diseases (Hallmann et al 2011), but also for their stress tolerance and improvement of plant growth in an extreme environmen (Forchetti et al 2010;Jha et al 2011;Karthikeyan et al 2012;Ali et al 2014;Naveed et al 2014a, b;Qin et al 2014;Cherif et al 2015). Phoenix dactylifera L. root endophytic bacteria that were isolated from the environment of desert oasis promoted plant growth under drought conditions (Cherif et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth promoting endophytic bacteria, for example, Burkholderia phytofirmans PsJN improve the growth of wheat and maize under drought conditions (Naveed et al 2014a, b). Endophytic bacterial strains Achromobacter xylosoxidans and Bacillus pumilus enhance the growth of sunflower seedlings under water stress (Forchetti et al 2010). The use of bacterial endophytes (Pseudomonas fluorescens YsS6 and P. migulae 8R6) has the potential to facilitate tomato plant growth under high salt contents (Ali et al 2014).…”
mentioning
confidence: 99%
“…In this regard, some authors presented a B. amyloliquefaciens strain able to modulate gene expression in rice plants during salt stress [31]. For a similar purpose, Forchetti et al [32] mentioned two Bacillus pumilus strain producing salycilic acid that simultaneously helped plants during water stress, stimulated sunflower growth, and inhibited the growth of Alternaria sp., Sclerotinia sp., and Verticillum sp. pathogenic fungi.…”
Section: International Journal Of Environment Agriculture and Biotecmentioning
confidence: 99%